Securing electronic commerce reducing the SSL overhead. - Apostolopoulos, G. (IEEE Network : the magazine of global information exchange)
The last couple of years have seen a growing momentum toward using the Internet for conducting business. Web-based electronic commerce applications are one of the fastest growing segments of the Internet today. A key enabler for e-commerce applications is the ability to setup secure private channels over a public network. The Secure Sockets Layer protocol provides this capability and is the most widely used security protocol in the Internet. We take a close look at the working principles behind SSL with an eye on performance. We benchmark two of the popular Web servers in wide use in a number of large e-commerce sites. Our results show that the overheads due to SSL can make Web servers slower by a couple of orders of magnitude. We investigate the reason for this deficiency by instrumenting the SSL protocol stack with a detailed profiling of the protocol processing components. In light of our observations, we outline architectural guidelines for large e-commerce sites